Discriminación Contra Las Mujeres En El Estado De Hidalgo, México: Una Revisión De La Última Encuesta Nacional Sobre Discriminación - Carlos Mejía Reyes; Karina Pizarro Hernández; Adrián Galindo Castro (European Scientific Journal, ESJ, 2017)
Discrimination against women is a structural phenomenon that international organizations have tried to eradicate through different legal instruments. In this regard, Mexico has signed several treaties and despite such initiatives, the discriminatory practice continues to diminish the fundamental rights of half of the population. Based on the interests of the state of Hidalgo (Mexico), this social phenomenon is regarded to be very crucial. The treatment of the subject is carried out by means of a quantitative review, and by comparing the last National Survey on Discrimination of the sub-sample of the State of Hidalgo with the national results. The analysis of the situation in a federative entity allows us to approach, in a diagnostic way, a phenomenon that is approached a little by the social sciences of the context. This research is the product of the "Diagnosis of discrimination in Pachuca de Soto, Hidalgo, and conurbada zone" project, and it was funded by the PROMEP of the Undersecretary of Higher Education.